Il presepe napoletano del Settecento e la Spagna: acquisizioni, collezionismo, tutela - Ebanista, Lorenzo (Diciottesimo Secolo, 2020)
The diffusion in Spain of crèche collections and Nativity scenes from Naples is undoubtedly linked to the common historical and cultural roots of the two countries and can be traced back to the viceregal period. However, the phenomenon became more generalized during the 18th century thanks to the direct involvement of the Royal family. In addition to the understandable desire to emulate what happened at court, the commissioning to Neapolitan artists and craftsmen of specific figures testifies to the existence of detailed plans for the preparation of the Spanish crèche sets. Other collections were subsequently put together during the 19th and the 20th centuries comprising select pieces belonging to some of the members of the Royal family and new acquisitions purchased from the antiques market or directly from well-known Neapolitan collectors. Most of these collections later became part of the public heritage, making Spain a virtuous example for the preservation of the Neapolitan crèche.